2018
DOI: 10.5194/acp-2018-624
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of humidity biases on light precipitation occurrence: observations versus simulations

Abstract: <p><strong>Abstract.</strong> This work uses a network of GPS stations over Europe from which a homogenised integrated water vapor (IWV) dataset has been retrieved, completed with colocated temperature and precipitation measurements over specific stations to i) estimate the biases of six regional climate models over Europe in terms of humidity; ii) understand their origins; iii) and finally assess the impact of these biases on the frequency of occurrence of precipitati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 47 publications
2
10
0
Order By: Relevance
“…In spring, the weather is drier with fewer rainy days, but slightly more extremes. This is consistent with the decrease in relative humidity that affects the triggering of precipitation (Rasmussen et al, 2017;Bastin et al, 2019).…”
Section: Precipitationsupporting
confidence: 85%
See 1 more Smart Citation
“…In spring, the weather is drier with fewer rainy days, but slightly more extremes. This is consistent with the decrease in relative humidity that affects the triggering of precipitation (Rasmussen et al, 2017;Bastin et al, 2019).…”
Section: Precipitationsupporting
confidence: 85%
“…The analysis of precipitation can be sensitive to these differences and to local effects. It is expected that the decrease in relative humidity observed in the Paris area affects some indices of precipitation, especially indices concerning occurrence (Bastin et al, 2019).…”
Section: Annual Trendsmentioning
confidence: 99%
“…More recently, the value of continuous long time series of GPS IWV data has been investigated for the purpose of studying global and regional climate variability and validating climate models (Nilsson and Elgered, 2008;Vey et al, 2009;Roman et al, 2012;Ning et al, 2013;Chen and Liu, 2016;Wang et al, 2016;Parracho, 2017;Bastin et al, 2018). These studies reported various levels of agreement between GPS and atmospheric models/reanalyses making it difficult to draw general conclusions on the consistency between products.…”
Section: Introductionmentioning
confidence: 99%
“…The core set aimed at covering four possible combinations of differences in the climate conditions, namely, cooler and moister conditions, cooler and dryer conditions, warmer and moister conditions, as well as warmer and dryer conditions. Previous observational and global model studies suggest that temperature and moisture are considerably positively correlated in most regions around the globe and trends lie around 7% change in moisture per K change in temperature, reflecting the Clausius-Clapeyron rate for increases in moisture and maintains a quasi-constant relative humidity (Bastin et al, 2019;Willett et al, 2010). In Europe, the scaling of moisture to temperature is slightly higher (section 2.3.2).…”
Section: Perturbation Analysismentioning
confidence: 88%
“…The perturbations of moisture were implemented under consideration of the close relationship between temperature and water vapor in the atmosphere, thus, taking into account the respective temperature perturbation (e.g. Willett et al, 2010;Bastin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%